Social support, social undermining, and acute clinical pain in women: Mediational pathways of negative cognitive appraisal and emotion. (November 2020) - Gaffey, Allison E; Burns, John W; Aranda, Frances; Purim-Shem-Tov, Yanina A; Burgess, Helen J; Beckham, Jean C; Bruehl, Stephen; Hobfoll, Stevan E
Women may be disproportionately vulnerable to acute pain, potentially due to their social landscape. We examined whether positive and negative social processes (social support and social undermining) are associated with acute pain and if the processes are linked to pain via negative cognitive appraisal and emotion (pain catastrophizing, hyperarousal, anger). Psychosocial variables were assessed in inner-city women ( N = 375) presenting to an Emergency Department with acute pain. The latent cognitive-emotion variable fully mediated social undermining and support effects on pain, with undermining showing greater impact. Pain may be alleviated by limiting negative social interactions, mitigating risks of alternative pharmacological interventions.